Do EU structural funds promote regional employment? Evidence from dynamic panel data models - Mohl, Philipp; Hagen, Tobias (Frankfurt am Main, 2011)
"Despite its rather broad goal of promoting “economic, social and territorial cohesion”, the existing literature has mainly focused on investigating the Cohesion Policy’s growth effects. This ignores the fact that part of the EU expenditures is directly aimed at reducing disparities in the employment sector. Against this background, the paper analyses the impact of EU structural funds on employment drawing on a panel dataset of 130 European NUTS regions over the time period 1999-2007. Compared to previous studies we (i) explicitly take into account the unambiguous theoretical propositions by testing the conditional impact of structural funds on the educational attainment of the regional labour supply, (ii) use more precise measures of structural funds for an extended time horizon and (iii) examine the robustness of our results by comparing different dynamic panel econometric approaches to control for heteroscedasticity, serial and spatial correlation as well as for endogeneity. Our results indicate that high-skilled population in particular benefits from EU structural funds."